2016
DOI: 10.1186/s13104-016-1986-6
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence and its associated factors among married women of a village development committee of rural Nepal

Abstract: BackgroundViolence against women is a global public health problem occurring in multitude of contexts and domestic violence is considered to be the most pervasive one. Poor enforcement of policies, limitation of researches and expertise in this field largely accounts for persistence of this problem and nature of domestic violence and its associated factors are poorly understood.ObjectivesThis research aimed to estimate the magnitude of different forms of domestic violence and identify its associated factors.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
60
7
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 27 publications
(32 reference statements)
11
60
7
3
Order By: Relevance
“…In agreement, [14] we found that a husbandwife age difference more than 10 years was significantly associated with DV which was confirmed by results of univariate regression analysis. As regard working status of the husband, several previous studies [13,[20][21][22] failed to link DV to working status of the husband, similar to our results. These findings are quit strange, especially when considering that money as a cause of DV was reported by more than half the abused women.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement, [14] we found that a husbandwife age difference more than 10 years was significantly associated with DV which was confirmed by results of univariate regression analysis. As regard working status of the husband, several previous studies [13,[20][21][22] failed to link DV to working status of the husband, similar to our results. These findings are quit strange, especially when considering that money as a cause of DV was reported by more than half the abused women.…”
Section: Discussionsupporting
confidence: 91%
“…This is because financial independency of the woman is supposed to be protective against DV, moreover, these women who were dependent on their husband for their basic demands, usually accept and tolerate the violence committed against them. However, our results are inconsistent, [5,[20][21][22] where economic independency and presence of ownership were linked to DV and not the opposite which may be explained by different socioeconomic context in which these studies were conducted.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations